Pengendalian Sanitasi Kapal Motor di Pelabuhan Tanjung Emas Semarang - Karolus Geleuk Sengadji; Mustholiq Mustholiq; Santika Aprilliani Ratna Dewi; Gloria Hermiana Helen (Dinamika Bahari, 2022)
Sanitation is one of the efforts aimed at environmental risk factors on ships to break the chain of disease transmission in order to maintain and improve public health and maritime environment. This study aimed to determine the extent of the role of the master and crew in carrying out the provisions of MARPOL 73/78, annex IV and annex V in order to maintain the cleanliness of the ship and protect the maritime environment and to know the role of the Kantor Kesehatan Pelabuhan (KKP) in terms of providing waste disposal facilities or waste to control sanitation on board. The research method in discussing this problem uses qualitative methods. The qualitative method describes part of ships by inspecting and assessing how high the level of risk that can endanger the health of passengers onboard. Based on the results of the study, it can be concluded that Captain has been responsible for safety, smoothness and comfort of passengers on board and all crews always maintains sanitation on board and supervision of the provision of clean water and drinking water has been carried out in accordance with Standard Operating Procedures (SOP) by providing good facilities and infrastructure.